Psychiatric emergency referrals in a tertiary care hospital - Gagandeep Singh; Suprakash Chaudhury; Daniel Saldanha; Vasdev Singh; Shivaji Marella; Rajeshwari Vhora (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2018)
Background: Acute psychiatric emergencies such as excitement, violence, stupor, and suicidal attempts, previously the domain of mental hospitals, are now handled by the general hospital psychiatric units. There is a paucity of Indian data concerning psychiatric emergency referrals. Aim: The aim is to study psychiatric emergency referrals in a teaching hospital. Materials and Methods: This hospital-based, descriptive study was undertaken in Emergency Medicine and Psychiatry Departments of a tertiary care hospital during the period of November 2016 to April 2017. All patients were first evaluated by the postgraduate resident on duty of Emergency Medicine Department and triaged using mental health triage scale (MHTS). The total sample size was 60. Sociodemographic particulars of patients and reason of referral were recorded on a special proforma, and the Brief Psychiatric Rating Scale (BPRS) was administered. Psychiatric diagnoses were made according to the International Classification of Disease, 10th Revision Diagnostic Criteria for Research. Results: Out of total 60 patients, 70% were males and 30% female. Most of the patients (41.7%) belonged to the age group of 31–40 years and 53.3% were married. Majority (61%) were referred by family members while 25% were referred by a nonpsychiatric medical professional. The most common reason for psychiatric referral was the presence of coexisting mental symptoms along with physical illness (38%) while 25% were referred as they had predominant psychiatric symptoms. The most common triage category was yellow (38%) and the least common was red category. Schizophrenia (33.3%) was the most common psychiatric diagnosis, followed by alcohol dependence (25%) and mania (16.7%). There was a significant correlation of BPRS score to severity according to triage. Conclusions: The common psychiatric disorders seen in Emergency Department (ED) are schizophrenia, substance use disorder, and mania. MHTS can be easily used by ED doctors for quick and appropriate triage of patients with psychiatric symptoms.